(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the influence of adjuvants associated with the spray mixture of insecticides aimed at the control of Euschistus heros in the soybean crop. First the treatments were applied and later the cages were assembled, being artificially infested 10 insects per cage. The treatments were composed of the insecticide Engeo Pleno® in combination with different adjuvants. The surface tension was reduced in all the treatments that contained the addition of adjuvants, and the treatments with organosilicone were the ones that resulted in the lower levels. The treatments did not present a significant difference, however, a superior efficiency of the insecticide was observed in association with adjuvants. The addition of Assist®, Break Thru® S240 and TA35® adjuvants to the thiamethoxam + lambda-cyhalothrin insecticide improves the control of Euschistus heros, showing an agronomic efficiency superior to the insecticide applied alone.